Relationship Between Characteristics of Pregnant Women and Pregnant Women Class Participation at The Panombeian Panei Health Center, Panombeian Panei District, Simalungun Regency, 2022 - Yanti (International Archives of Medical Sciences and Public Health, 2023)
The class for pregnant women is a study group for expectant mothers about overall health for pregnant women. The purpose of the class for pregnant women is to educate pregnant women so that they can go through the process of pregnancy and childbirth smoothly, as well as go through the early phases of the baby's life with the provision of basic knowledge. This study aims to determine the relationship between the characteristics of pregnant women and the class participation of pregnant women. This research is an analytic research with cross sectional study design. The population in this study were all pregnant women at the Panombeian Panei Health Center as many as 53 people. The sample in this study uses total sampling. Data collection was carried out by distributing questionnaires to respondents. Data processing by editing, coding, entering, cleaning and tabulating data. Data analysis used the chi square test. The results showed that there was no correlation between parity (p=0.371) and class participation for pregnant women. There is a relationship between age (p=0.008), occupation (p=0.000) and pregnant women's class participation. Thus it is suggested to pregnant women to conduct counseling to health workers regarding the benefits of participating in pregnant women classes